2013
DOI: 10.1590/s0103-84782013005000053
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização de acessos de mangueira Ubá na Zona da Mata Mineira

Abstract: RESUMO Objetivou-se realizar a caracterização física e química de acessos de manga Ubá na região da Zona da Mata de Minas Gerais, visando a identificar materiais de interesse industrial. Frutos fisiologicamente maduros foram colhidos e transportados para o Laboratório de 7, 11, 16, 17, 21, 26, 28, 47, 48, 53, 54 7, 11, 16, 17, 21, 26, 28, 47, 48, 53, 54 and 56

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
(4 reference statements)
2
2
2
2
Order By: Relevance
“…Hence, both the biochemical process and CO 2 fixation are damaged by increased leaf temperature. Oliveira et al (2013), evaluating soluble sugar contents over the fruit development period, found the mean value of 37 mg g -1 of dry matter in leaves, a higher result than the one found in our study. Evaluating physiological traits, in terms of doses applied via irrigation, it is possible to see that the doses did not have a significant interaction with samplings.…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…Hence, both the biochemical process and CO 2 fixation are damaged by increased leaf temperature. Oliveira et al (2013), evaluating soluble sugar contents over the fruit development period, found the mean value of 37 mg g -1 of dry matter in leaves, a higher result than the one found in our study. Evaluating physiological traits, in terms of doses applied via irrigation, it is possible to see that the doses did not have a significant interaction with samplings.…”
Section: Resultscontrasting
confidence: 95%
“…Paclobutrazol increased the percentage of flowering in plants and, consequently, the consumption of carbohydrates for the formation and development of panicles, resulting in lower carbohydrate contents in leaves. Oliveira et al (2013), evaluating the total soluble sugar contents in leaves over the tumescence period of floral gems, obtained a different behavior from the one found here: a quadratic reduction, in terms of different paclobutrazol doses. The lowest soluble sugar content was 33 mg g -1 of dry matter in leaves of 'Ubá' mango tree, which corresponds to the dose of 1.76 g of paclobutrazol per linear meter of canopy.…”
Section: Resultscontrasting
confidence: 85%
“…Similar values were observed by some authors for 'Ubá' mango trees in the "Zona da Mata" region (Oliveira et al 2013, Rufini et al 2010, who found mean values between 18.8 and 65. The ratio has been used to evaluate the fruit flavor, as it increases with maturation (Chitarra & Chitarra 2005).…”
supporting
confidence: 90%
“…The mean pulp yield of fruits was 65 %, being close to values found by Silva et al (2009) and Oliveira et al (2013), from 61 % and 69 %, respectively, for the 'Ubá' cultivar. The use of fruits with high pulp yields is important for industrial processing.…”
supporting
confidence: 88%
“…The explanation for the differences found in the two studies for this cultivar may lie in ripeness stage at time of harvest. Silva et al (2009) Oliveira et al (2013), the carotenoids found in the fruit of 46 Ubá mangoes varied between 0.61 and 2.12 mg 100g -1 pulp.…”
Section: Bioactive Compoundsmentioning
confidence: 95%